Pengolahan Data Pembayaran Upah Karyawan Berbasis Web - Rana Putra Sawindo; Megawaty (STMIK Budi Darma, 2023)
Constraints encountered in the process of managing data on employee wages and salaries at PT. Agung Cempaka Guna, namely starting from recording the number of employees, the process of calculating wages and salaries, and calculating sales commissions by marketing is still done manually, so errors often occur both in the calculation process and in the recap of total wages and salaries. In addition, the data collection process, which was carried out both with notes in books and input data in excel files, was still separated and not yet integrated, making it difficult for the process of making reports and also causing wastage of paper and ink. This study aims to build an employee wage data processing application in order to facilitate the process of managing employee wage and salary data and to facilitate the process of compiling employee salary reports. This application is built on a web basis with the PHP programming language and uses the MySQL database, and uses the Unified Modeling Language (UML)